The Evolution of High Incomes in Northern America: Lessons from Canadian Evidence - Saez, Emmanuel; Veall, Michael R (American Economic Review, 2005)
The Evolution of High Incomes in Northern America: Lessons from Canadian Evidence by Emmanuel Saez and Michael R. Veall. Published in volume 95, issue 3, pages 831-849 of American Economic Review, June 2005